Cause of death varies across Australia, New Zealand and Malaysia in those on renal replacement therapy - Results from the Study of Heart And Renal Protection-Extended Review (SHARP-ER) - Talbot, B; Sukkar, L; Smyth, B; Jun, M; Jardine, M; Cass, A; Walker, R; Reith, C; Hooi, L; Gallagher, M (American Society for Nephrology, 2018)
The mortality rate among dialysis patients is high with regional variability. The Study of Heart and Renal Protection-Extended Review (SHARP-ER) comprised extended 5-year follow up of eligible participants in Australia, New Zealand and Malaysia alive at the end of SHARP (a randomised double-blind trial of simvastatin and ezetimibe vs. placebo in chronic kidney disease). We compared survival and cause of death between countries in dialysis patients in the SHARP-ER cohort.